2018
DOI: 10.21831/jser.v2i1.19333
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inquiry-Based Interactive Demonstration Learning Model on VIII Grade Students’ Higher Order Thinking Skill

Abstract: Teacher’s domination in teaching science subject is still found in many schools, including junior high schools. Since then, students experience a lack of direct observation leading to not only their low conceptual understanding, but also their higher order thinking ability. Therefore, the implementation of a proper learning model becomes a crucial breakthrough. In this present paper, we focus on the influence of learning model with inquiry level of interactive demonstration (as the experimental class) and disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 4 publications
(5 reference statements)
1
6
0
2
Order By: Relevance
“…Guru cenderung mendikte peserta didik selama di kelas. Oleh sebabnya, peserta didik mengalami kekurangan pengalaman observasi berbasis langsung selama proses mengeksplorasi konsep dan detail penting (Yulianti et al, 2018). Dalam pembelajaran yang ada pada kelaskelas konvensional, pembelajaran hanya berpusat pada guru yang notabene berorientasi pada penjelasan materi dan contoh soal.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Guru cenderung mendikte peserta didik selama di kelas. Oleh sebabnya, peserta didik mengalami kekurangan pengalaman observasi berbasis langsung selama proses mengeksplorasi konsep dan detail penting (Yulianti et al, 2018). Dalam pembelajaran yang ada pada kelaskelas konvensional, pembelajaran hanya berpusat pada guru yang notabene berorientasi pada penjelasan materi dan contoh soal.…”
Section: Pendahuluanunclassified
“…Jadi, seluruh analisis kuantitatif membuktikan bahwa optimalisasi kemampuan siswa untuk bernalar secara ilmiah dapat dilakukan dengan menaplikasikan model pembelajaran yang berorientasi pada siswa, seperti model inkuiri secara terbimbing. Ini sejalan dengan temuan sebelumnya dengan fokus pada kemampuan berfikir tingkat tinggi (Yulianti et al, 2018 Detail jawaban benar siswa untuk setiap butir soal diberikan dalam Gambar 2. Peningkatan kemampuan penalaran ilmiah peserta didik dapat diketahui dari peningkatan jawaban benar.…”
Section: Hasil Dan Pembahasanunclassified
“…The direct involvement of students in learning can improve learning outcomes and thinking skills [32]. Various studies have shown that the use of inquiry-interactive demonstration models can improve learning outcomes [33], problem solving skill [34], high order thinking skill [23], and reduce student misconception [35]. Furthermore, the effectivity of using instructional module seen by N-Gain score result in each indicators of critical thinking skill.…”
Section: Validation Resultsmentioning
confidence: 99%
“…The instructional module implementation phase is in the operational field trials carried out by conducting learning using modul as learning objects with the subject used is student of VII A and VII B class in SMP Negeri 20 Surakarta school year 2019/2020. Implementing modul as learning objects in the classroom to find out the improvement of students' critical thinking skills using pretest and postest design [23]. The design of the chosen research method can be seen in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Students are invited to connect experiences with the concepts of science that will be built, so students will feel that the concepts of science really occur in their surroundings. Problem solving activities through a good understanding of concepts can help students strengthen their thinking patterns and develop their thinking abilities (Yulianti, et al 2018).…”
Section: Introductionmentioning
confidence: 99%